2019
DOI: 10.3389/fphar.2019.00923
|View full text |Cite
|
Sign up to set email alerts
|

Xinmailong Modulates Platelet Function and Inhibits Thrombus Formation via the Platelet αIIbβ3-Mediated Signaling Pathway

Abstract: Background: Xinmailong (XML), a bioactive composite extracted from Periplaneta americana , has been widely used to treat cardiovascular diseases such as congestive heart failure. However, it is unclear whether XML has antiplatelet and antithrombotic effects. Methods: The effects of XML on agonist-induced platelet aggregation, adhesion and spreading, granule secretion, integrin α II bβ3 activation, and thrombus formation were evaluated. Phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…The anti-myocardial ischemia effect of Xinmailong may be related to the antiplatelet aggregation. Some research showed that platelet adherence to immobilized collagen-coated surfaces was decreased by Xinmailong and it inhibited collagen-, thrombin-, and AA-induced platelet aggregations in a dose-dependent fashion ( Wang et al, 2019 ). In addition, Xinmailong was reported to reduce myocardial expression of hypoxia-induced factor-1α (HIF-1α) and decrease plasma endothelin-1 (ET-1) levels, so as to alleviate hypoxia-ischemic myocardial injury ( Qi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-myocardial ischemia effect of Xinmailong may be related to the antiplatelet aggregation. Some research showed that platelet adherence to immobilized collagen-coated surfaces was decreased by Xinmailong and it inhibited collagen-, thrombin-, and AA-induced platelet aggregations in a dose-dependent fashion ( Wang et al, 2019 ). In addition, Xinmailong was reported to reduce myocardial expression of hypoxia-induced factor-1α (HIF-1α) and decrease plasma endothelin-1 (ET-1) levels, so as to alleviate hypoxia-ischemic myocardial injury ( Qi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A series of clinical trials performed in HF patients confirmed the effectiveness of Xinmailong in improving cardiac function, such as enhancement of myocardial contraction and inhibition of ventricular remodeling ( Lu et al, 2018 ). It was reported that Xinmailong could inhibit platelet function and has antithrombotic activity, could be a potential therapeutic candidate to prevent or treat platelet-related cardiovascular diseases ( Wang et al, 2019 ). Clinical outcome revealed that Xinmailong injection has certain protective effects on cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…As the ECM hydrogels derived form porcine skin possesses good plasticity, injectability, biocompatibility and renewability, it can be applied to irregular skin tissue injuries and accelerate tissue healing [ [26] , [27] , [28] , [29] ]. Moreover, ECM is closely related to thrombosis [ 30 ]; under certain physiological conditions, the exposure of subcutaneous ECM and the subsequent platelet accumulation influence the control of hemorrhage [ [31] , [32] , [33] ]. Thus, ECM proteins (including fibrin, fibronectin, collagen, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometric assays were performed as described previously ( Wang et al, 2019 ). ADP-stimulated P-selectin exposure and fibrinogen binding were determined in washed platelets.…”
Section: Methodsmentioning
confidence: 99%